2020
DOI: 10.3390/genes11010069
|View full text |Cite
|
Sign up to set email alerts
|

A New Assessment of Thioester-Containing Proteins Diversity of the Freshwater Snail Biomphalaria glabrata

Abstract: Thioester-containing proteins (TEPs) superfamily is known to play important innate immune functions in a wide range of animal phyla. TEPs are involved in recognition, and in the direct or mediated killing of several invading organisms or pathogens. While several TEPs have been identified in many invertebrates, only one TEP (named BgTEP) has been previously characterized in the freshwater snail, Biomphalaria glabrata. As the presence of a single member of that family is particularly intriguing, transcriptomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 85 publications
3
18
0
Order By: Relevance
“…The C1q molecule found in invertebrates can act as a PRR, recognize multiple PAMPs, and participate in innate immune response 21 . A recent study also confirmed that macroglobulin plays an innate immunity role in mollusks 22 . In this study, the structures of the chitin‐binding protein, C1q protein domain, and A2M protein domain changed significantly under OA stress, which may indicate that P. canaliculata can resist OA stress through multiple mechanisms of immune response.…”
Section: Discussionsupporting
confidence: 67%
“…The C1q molecule found in invertebrates can act as a PRR, recognize multiple PAMPs, and participate in innate immune response 21 . A recent study also confirmed that macroglobulin plays an innate immunity role in mollusks 22 . In this study, the structures of the chitin‐binding protein, C1q protein domain, and A2M protein domain changed significantly under OA stress, which may indicate that P. canaliculata can resist OA stress through multiple mechanisms of immune response.…”
Section: Discussionsupporting
confidence: 67%
“…Faced with a wide variety of pathogens, the diversification of immune molecules appears to be the evolutionary path considered in invertebrates to mount a specific and effective defense response ( 99 , 124 126 ). In Biomphalaria , some large repertoires of genes that encode immune receptors such as FREPs, Toll-like receptor (TLR) or TEPs have been reported with more than 30, 50 or 11 genes respectively ( 46 , 63 , 99 , 127 ), while the number of effector genes identified may appear more restricted ( 128 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some molecules of this proto-complement have been characterized from several mollusk species like Complement factor C2/B from Bivalvia such as Ruditapes decussates ( 147 ) or Sinonovacula constricta ( 148 ), C3-like factors from mussels ( 149 ) or clams ( 150 ), but few studies led to the characterization of the whole system ( 145 , 151 ). While a diversity of C3-like proteins within the TEP superfamily has been reported ( 63 , 99 ) as well as a large repertoire of carbohydrate-binding proteins such as FREPs ( 46 , 152 ) and VIgL domain-containing proteins in B. glabrata ( 53 , 112 ), no complement factor C2/B-like protein has yet been identified. As the small lobe from several biomphalysins is structurally close to the CCP domain of Factor B, we speculated that biomphalysins could be involved in the activation of the proto-complement system by binding with TEPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is functional redundancy between members of the same multigene family. Recently, it was highlighted that BgTEP1 belongs to a multigenic family harboring at least ten other members comprising three C3-like complement factors, one alpha-2-macroglobulin, two macroglobulin complement-related proteins, four insect-like TEP including BgTEP1 and one CD109 molecule ( Castillo et al, 2020 ; Duval et al, 2020 ). In many invertebrate organisms, several genes encoding TEPs have been identified, fifteen from Anopheles gambiae , six from Drosophila melanogaster or nine from the tick Ixodes ricinus genomes, to name a few examples.…”
Section: Discussionmentioning
confidence: 99%